Memaksimalkan Canva Untuk Pembuatan Konten Gambar Sebagai Promosi UMKM di Media Sosial - Dhimas Suryo Laksono; Alanjono Astian Jondy Jondy; Jodi Caesar; Meidhi S Gultom; Tamara Yuliani (Jurnal Sinergi Sistem Informasi Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the national economy, especially in job creation and local economic development. However, many MSMEs still face challenges in leveraging digital technology, particularly in creating engaging visual content for social media promotion. This Community Service activity aims to enhance the skills of MSME actors in utilizing the Canva graphic design platform to produce effective and appealing promotional content. The training was conducted face-to-face for one day at Taman Baca Kota Depok, involving 20 MSME participants from various business sectors. The method employed a participatory and hands-on approach based on andragogical principles. Results from the training indicated significant improvements in participants’ understanding and design skills, as well as increased enthusiasm for using social media as a marketing tool. This activity is expected to support MSMEs in independently and sustainably digitalizing their promotions.